Hard miles [videorecording (DVD)] - Hanna, R. J. Daniel; Sander, Christian (Film producer); Modine, Matthew; McWilliams, Cynthia Kaye; Guillory, Jahking; Baker, Leslie David; Astin, Sean; Kelly, Jackson (Breaking Glass Pictures, 2024)
Hard Miles tells the uplifting true story of the bicycling team at Rite of Passage's Ridge View Academy, a medium-security correctional school in Colorado. The film Follows beleaguered coach Greg Townsend as he rounds up an unlikely crew of incarcerated students for a seemingly impossible bike ride from Denver to the Grand Canyon.